2020
DOI: 10.3390/jcm9030642
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hyperoxyphobia: Justified or Not? Benefits and Harms of Hyperoxia during Surgery

Abstract: The use of an inspiratory oxygen fraction of 0.80 during surgery is a topic of ongoing debate. Opponents claim that increased oxidative stress, atelectasis, and impaired oxygen delivery due to hyperoxic vasoconstriction are detrimental. Proponents point to the beneficial effects on the incidence of surgical site infections and postoperative nausea and vomiting. Also, hyperoxygenation is thought to extend the safety margin in case of acute intraoperative emergencies. This review provides a comprehensive risk-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 81 publications
0
17
0
1
Order By: Relevance
“…Thus, some controversy exists regarding "routine" supplemental oxygen administration following surgery. However, the clinical significance of such potentially harmful effects during the postoperative period has remained uncertain [23].…”
Section: Possible Harmful Effects Of Postoperative Hyperoxemic Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some controversy exists regarding "routine" supplemental oxygen administration following surgery. However, the clinical significance of such potentially harmful effects during the postoperative period has remained uncertain [23].…”
Section: Possible Harmful Effects Of Postoperative Hyperoxemic Oxygenmentioning
confidence: 99%
“…Additionally, follow-up studies of the PROXI trial [ 43 ], one of the largest RCTs with the lowest possible risk of bias and arguably the best designed trial conducted to date, found that 80% oxygen administration during the perioperative period was associated with significantly increased long-term mortality [ 44 ], shorter time to cancer recurrence or death [ 45 ], and long-term risk of myocardial infarction [ 46 ]. Thus, concerns regarding high FIO 2 and maintenance of hyperoxemia during and after surgery have still persisted [ 8 , 23 , 39 ].…”
Section: Prevention Of Surgical Site Infectionmentioning
confidence: 99%
“…Perioperative hypothermia induces poor tissue perfusion, and several strategies have been proposed to avoid it, including preoperative or intraoperative warming [164,165]. A benefit of perioperative hyperoxia in non-critically ill adults has not been demonstrated [166].…”
Section: Intraoperative Care For Tja Patientsmentioning
confidence: 99%
“…Another very recently published paper still advocates hyperoxia in noncritically ill intubated adult surgical patients ( Weenink et al, 2020 ). The unclear risk-benefit ratio led Meyhoff and others to stress the need of large trials to obtain the required statistical power to evaluate the effects on SSIs ( Meyhoff et al, 2011 ; Cohen et al, 2018 ; Meyhoff, 2019 ).…”
Section: Therapeutic Strategies: Where Do We Stand and What Is The Fumentioning
confidence: 99%